Assessment of HIV prevalence in Adults Within the Aliade Community, Benue State. - Oboli, Deborah; Gbuchie, Monica Anurika; Nyingifa, Tonte; Mkpae, Oluchi (International Journal of Medical Students, 2025)
BACKGROUND: Benue State is recognized as one of Nigeria’s high-risk zones for HIV, with an estimated prevalence of 4.8% among adults aged 15-64 years. The prevalence is notably higher among females at 6.3% and lower among males at 3.5%, making it the second highest HIV prevalence state in Nigeria. Despite relatively high awareness levels, the infection rate continues to rise in rural areas. This study focused on Aliade, a community in the TIV land, conducting random HIV testing on 500 adult outpatients aged 15-64 years over a period of five months, with Aliade General Hospital serving as the testing site. The study aimed to determine the HIV infection rate among adults in the Aliade community of Benue State, Nigeria, by assessing the prevalence of HIV. METHODS: A hospital-based randomized study was conducted at Aliade General Hospital, Benue State. HIV testing was performed using the rapid diagnostic testing algorithm according to Nigeria’s National HIV testing guidelines, with seropositive samples confirmed by supplemental assays. Data was collected over five months and analyzed using IBM SPSS version 26. RESULTS: The study included 500 respondents with a mean age of 39.4 years. Of the participants, 215 were male and 285 were female. Over half were married, and approximately 70% had only secondary education. While 90% of respondents were aware of HIV, only 60% had previously undergone testing. The prevalence of HIV was 5.6% overall, with 6.7% among females and 3.3% among males. CONCLUSION: Despite awareness of HIV, the prevalence remains high and is increasing. This study underscores the need for enhanced awareness and intervention strategies to address the growing HIV epidemic in Benue State.